2017
DOI: 10.48550/arxiv.1701.04104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$^{57}$Fe Mössbauer study of stoichiometric iron based superconductor CaKFe$_4$As$_4$: a comparison to KFe$_2$As$_2$ and CaFe$_2$As$_2$

Sergey L. Bud'ko,
Tai Kong,
William R. Meier
et al.

Abstract: 57 Fe Mössbauer spectra at different temperatures between ∼ 5 K and ∼ 300 K were measured on an oriented mosaic of single crystals of CaKFe 4 As 4 . The data indicate that CaKFe 4 As 4 is a well formed compound with narrow spectral lines, no traces of other, Fe -containing, secondary phases in the spectra and no static magnetic order. There is no discernible feature at the superconducting transition temperature in any of the hyperfine parameters. The temperature dependence of the quadrupole splitting approxim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…CaKFe 4 As 4 undergoes superconductivity below T c ≃ 35 K without other phase transitions for 1.8 ≤ T ≤ 300 K. [15][16][17] The magnetic ground state of the normal state in CaKFe 4 As 4 is paramagnetic. 16,18) Various measurements 15,16,[18][19][20][21] indicated that CaKFe 4 As 4 shows behaviors similar to optimally or slightly overdoped (Ba 1−x K x )Fe 2 As 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CaKFe 4 As 4 undergoes superconductivity below T c ≃ 35 K without other phase transitions for 1.8 ≤ T ≤ 300 K. [15][16][17] The magnetic ground state of the normal state in CaKFe 4 As 4 is paramagnetic. 16,18) Various measurements 15,16,[18][19][20][21] indicated that CaKFe 4 As 4 shows behaviors similar to optimally or slightly overdoped (Ba 1−x K x )Fe 2 As 2 .…”
mentioning
confidence: 99%
“…CaKFe 4 As 4 undergoes superconductivity below T c ≃ 35 K without other phase transitions for 1.8 ≤ T ≤ 300 K. [15][16][17] The magnetic ground state of the normal state in CaKFe 4 As 4 is paramagnetic. 16,18) Various measurements 15,16,[18][19][20][21] indicated that CaKFe 4 As 4 shows behaviors similar to optimally or slightly overdoped (Ba 1−x K x )Fe 2 As 2 . Angle-resolved photoemission spectroscopy (ARPES) measurements supported by density functional theory calculations indicated that the Fermi surface consists of three-hole pockets at the Γ point and two electron pockets at the M point.…”
mentioning
confidence: 99%